The shields against suicidal attempts: experienced by university students in Malaysia - Mohd munir, Nur Syuhada; Rais, Haniza; Zubairi, Ainol Madziah (iConferences, 2024)
Intro: This study aims to explore how four suicide survivors’ experiences that prevented them from pursuing their suicide attempts. This study explored ways that they have been protected before, protecting them from their intention to commit suicide. Participants: Four university students, one female and three males, participated in this study through purposive sampling. Method: They were recruited using a specified criteria set and interviewed through a series of individual interview sessions. Findings: Thematic analysis of the interview series extracted six themes including professional support, technology assisted support, redirecting feelings into physical activities, spiritual consciousness, supportive circles, and feeling important. Conclusion: The highlighted findings retrieved from this research are expected to give insight to counselling and mental health professionals that can lead to holistic counselling and psychosocial support for early prevention and further intervention for those who are vulnerable.